Response to comment on "Magnetosensitive neurons mediate geomagnetic orientation in Caenorhabditis elegans" - Vidal-Gadea, Andres (eLife, 2018)
Many animals can orient using the earth’s magnetic field. In a recent study, we performed three distinct behavioral assays providing evidence that the nematode Caenorhabditis elegans orients to earth-strength magnetic fields (Vidal-Gadea et al., 2015). A new study by Landler et al. suggests that C. elegans does not orient to magnetic fields (Landler et al., 2018). They also raise conceptual issues that cast doubt on our study. Here, we explain how they appear to have missed positive results in part by omitting controls and running assays longer than prescribed, so that worms switched their preferred migratory direction within single tests. We also highlight differences in experimental methods and interpretations that may explain our different results and conclusions. Together, these findings provide guidance on how to achieve robust magnetotaxis and reinforce our original finding that C. elegans is a suitable model system to study magnetoreception.